Inflammation and innate immune function in critical illness. Issue 3 (June 2016) - Muszynski, Jennifer A.; Thakkar, Rajan; Hall, Mark W.
Abstract : Purpose of review: The purpose of review is to highlight the inflammatory response in critical illness and the importance of immune monitoring and modulation in the diagnosis and treatment of critical illness-induced innate immune suppression. Recent findings: The pro and anti-inflammatory responses are known to be concurrently activated in many patients requiring intensive care, with innate immune suppression emerging as an important, and potentially reversible, complication of critical illness. Summary: The initial inflammatory response to critical illness is typically driven by innate immune cells, including neutrophils, monocytes, and macrophages. The proinflammatory mediators made by these cells are responsible for many of the pathophysiologic features of critical illness. Concurrent with this, however, is a compensatory anti-inflammatory response, including the elaboration of anti-inflammatory mediators and impairment of innate immune cell function. This includes reduction of monocyte human leukocyte antigen-DR expression and impairment of the ability of innate immune cells to produce tumor necrosis factor alpha when stimulated ex vivo . In its most severe form this is referred to as immunoparalysis, and is associated with markedly increased risks for secondary infection and death in the ICU. Prospective testing can detect this phenomenon, and immunostimulatory strategies, including the use of granulocyte macrophage-colony stimulating factor, have the potential to restore innate immune function in this setting.